The Impact of Job Loyalty on Employee Job Performance: A Case Study of Almarai Company in the Kingdom of Saudi Arabia - Alharbi, Abdulaziz Mosleh (Journal of Economic, Administrative and Legal Sciences, 2025)
This study aims to examine the impact of employee loyalty on employee performance at Almarai Company in the Kingdom of Saudi Arabia, in light of the rapid changes in the business environment and the growing challenges associated with attracting and retaining talent. The problem of the study stems from the observation of low rates of job stability in some sectors, which raises questions about the extent to which employee loyalty affects actual employee performance. The importance of this study lies in shedding light on one of the psychological and behavioral factors influencing organizational success, as employee loyalty is a vital indicator that impacts productivity, job satisfaction, and reducing employee turnover rates. The study was based on the main hypotheses that there is a statistically significant positive relationship between employee loyalty and employee performance, and that manifestations of loyalty, such as the desire to continue working and a sense of organizational belonging, directly contribute to achieving organizational goals. The study used a quantitative approach, relying on a questionnaire distributed to a sample of 160 employees at Almarai Company, with the aim of collecting accurate quantitative data to support hypothesis testing. The results of the statistical analysis revealed a strong relationship between job loyalty and employees' willingness to remain with the company, reflecting a positive impact of loyalty on job stability. However, the results did not reveal a significant impact of job loyalty on either the sense of organizational belonging or the expected contribution to achieving organizational goals. Based on these findings, the study recommends enhancing the internal work environment by developing effective incentive programs, providing opportunities for professional growth, enhancing transparency in administrative communication, and establishing a positive organizational culture that supports loyalty and organizational belonging.
Keywords: job loyalty; job performance; willingness to stay; organizational affiliation; Almarai Company